Emodin inhibits growth and induces apoptosis in an orthotopic hepatocellular carcinoma model by blocking activation of STAT3 - Subramaniam, A.; Shanmugam, M.; Ong, T.; Li, F.; Perumal, E.; Chen, L.; Vali, S.; Abbasi, T.; Kapoor, S.; Ahn, K.; Kumar, Alan Prem; Hui, K.; et al. (Stockton Press, 2013)
BACKGROUND AND PURPOSE: Aberrant activation of STAT3 is frequently encountered and promotes proliferation, survival, metastasis and angiogenesis in hepatocellular carcinoma (HCC). Here, we have investigated whether emodin mediates its effect through interference with the STAT3 activation pathway in HCC. EXPERIMENTAL APPROACH: The effect of emodin on STAT3 activation, associated protein kinases and apoptosis was investigated using various HCC cell lines. Additionally, we also used a predictive tumour technology to analyse the effects of emodin. The in vivo effects of emodin were assessed in an orthotopic mouse model of HCC. KEY RESULTS: modin suppressed STAT3 activation in a dose- and time-dependent manner in HCC cells, mediated by the modulation of activation of upstream kinases c-Src, JAK1 and JAK2. Vanadate treatment reversed emodin-induced down-regulation of STAT3, suggesting the involvement of a tyrosine phosphatase and emodin induced the expression of the tyrosine phosphatase SHP-1 that correlated with the down-regulation of constitutive STAT3 activation. Interestingly, silencing of the SHP-1 gene by siRNA abolished the ability of emodin to inhibit STAT3 activation. Finally, when administered i.p., emodin inhibited the growth of human HCC orthotopic tumours in male athymic nu/nu mice and STAT3 activation in tumour tissues. CONCLUSIONS AND IMPLICATIONS: modin mediated its effects predominantly through inhibition of the STAT3 signalling cascade and thus has a particular potential for the treatment of cancers expressing constitutively activated STAT3.